Do fascial perturbations contribute to oxidative stress? - Peter Lelean CM (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
The existing paradigm for understanding the pathogenesis of both breast and ovarian cancer is that a small percentage of these neoplasias involve a genetic predisposition. The balance is lacking an attribution. The author proposes that the function of the lymphatic system in both areas is influenced by changed muscle strain patterns. When the muscle activity changes in the presence of altered strain patterns, there is a diminution of lymphatic drainage function affecting those tissues. The drainage function is augmented by muscle activity and the distribution of lymph node aggregation sites is weighted toward shoulder,